Association between pelvic obliquity and scoliosis, hip displacement and asymmetric hip abduction in children with cerebral palsy: a cross-sectional registry study - Gunnar Hägglund (BMC Musculoskeletal Disorders, 2020)
Abstract Background Pelvic obliquity (PO) is common in individuals with cerebral palsy (CP). The prevalence of PO in a population of children with CP and its associations with scoliosis, hip displacement and asymmetric range of hip abduction were analysed. Methods Over a 5-year period all pelvic radiographs from the Swedish surveillance programme for CP and the recorded data for scoliosis and hip abduction in children from southern Sweden at Gross Motor Function Classification System (GMFCS) levels II–V were analysed. PO and hip displacement calculated as migration percentage (MP) were measured on supine pelvic radiographs and compared with presence of scoliosis and side difference in hip abduction. Statistical analyses comprised chi-squared and binominal testing. Results In total, 337 children were analysed, of whom 79 had a PO of ≥5°. The proportion of children with PO increased from 16% in GMFCS level II to 34% in level V. Scoliosis combined with PO was reported in 38 children, of whom 34 (89%, 95% confidence interval [CI] 80–99%) had the convexity opposite to the high side of the PO. Asymmetric abduction with PO was reported in 45 children, of whom 40 (89%, CI 79–99%) had reduced abduction on the high side of the PO. Asymmetric MP of ≥5% with PO was seen in 62 children, of whom 50 had higher MP on the high side of the PO (81%, CI 71–90%). Children in GMFCS levels II–IV more often had isolated infra-pelvic association with PO (47% versus 19% in GMFCS V, P = 0.025), while combined supra- and infrapelvic association was more common in GMFCS level V (65% versus 30% in GMFCS II–IV, P = 0.004). Isolated infrapelvic or no association was seen in 74% of children ≤10 years of age while 76% of children ≥11 years old had suprapelvic or combined supra- and infrapelvic association with PO (P < 0.001). Conclusions There was a strong association between the high side of the PO and the side of scoliosis, highest MP, and lowest range of abduction when PO was measured in supine position. PO was more often associated with infrapelvic factors. PO was seen in young children indicating the need for early awareness of this complication.